2011
DOI: 10.2495/ehr110131
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory toxicity ofAspergillus versicolor: the most common indoor mould in Slovakia

Abstract: A mould Aspergillus versicolor clearly dominates in damp and mouldy indoor environments under Slovak dwelling/public building conditions (up to 1/3 of all isolates during the last decade's surveys). Nearly all of its isolates are able to synthesize a mycotoxin sterigmatocystin (detected by LC/MS-MS), that showed severe in vitro as well as in vivo toxic potential in animal experiments (after intratracheal instillation to rats). In vitro toxicity of complex chloroformextractable endo-and exometabolites of 10 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Additionally, a study developed by Miller et al (2010), which considered exposure of STC via the indoor environment, concluded that following inhalation (intratracheal installation) of STC, a non-specific but severe inflammatory response of the lung tissue was observed. Similarly, severe cytotoxic and inflammatory damage of lung tissue as well as breaking down of self-cleaning mechanism of airways in rats in vivo were observed after intratracheal instillation of STC containing complex extrolites of an A. versicolor strain of indoor origin in the studies by Piecková et al (2011Piecková et al ( , 2015.…”
Section: Toxicity Of Stcmentioning
confidence: 87%
“…Additionally, a study developed by Miller et al (2010), which considered exposure of STC via the indoor environment, concluded that following inhalation (intratracheal installation) of STC, a non-specific but severe inflammatory response of the lung tissue was observed. Similarly, severe cytotoxic and inflammatory damage of lung tissue as well as breaking down of self-cleaning mechanism of airways in rats in vivo were observed after intratracheal instillation of STC containing complex extrolites of an A. versicolor strain of indoor origin in the studies by Piecková et al (2011Piecková et al ( , 2015.…”
Section: Toxicity Of Stcmentioning
confidence: 87%